Penyelesaian Masalah Pendistribusian Barang Menggunakan Algoritma Bee Colony Optimization (Jurnal EurekaMatika, 2018)
In this paper, a distribution problem in order to get an optimum route with shortest distance using Bee Colony Optimization Algorithm is solved. We consider a distribution problem with a single distributor and multi consumer. The bee colony optimization algorithm is an algorithm which is adapted from the behaviour of colony of bees in searching their food. Employed bees will collecting food and doing bee dance to invite onlooker bees to collect food in a source. When there’s no food left in the food source, employed bees will become scouts to search for a new source. The result shows that the algorithm successfully applied to solve the distribution problem and can produce an optimum solution.ABSTRAKArtikel ini membahas penyelesaian masalah pendistribusian barang agar diperoleh sebuah rute dengan jarak terpendek menggunakan Algoritma Bee Colony Optimization. Masalah pendistribusian yang dibahas adalah masalah pendistribusian dengan satu distributor dan banyak konsumen. Algoritma Bee Colony Optimization diadaptasi dari kehidupan koloni lebah dalam mencari makanan. Lebah pekerja akan mengambil makanan dan melakukan tarian untuk mengajak lebah pencari agar ikut mengambil makanan di suatu sumber makanan. Ketika sumber makanan habis, lebah pekerja akan berubah menjadi lebah pengintai untuk mencari sumber makanan baru. Hasil implementasi menunjukkan bahwa Algoritma Bee Colony Optimization berhasil diterapkan untuk menyelesaikan masalah pendistribusian barang dan dapat menghasilkan solusi yang cukup baik.
Keywords: Pendistribusian Barang; Travelling Salesman Problem; Algoritma Bee Colony Optimization; Solusi Optimal